2020
DOI: 10.1159/000508533
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Response to Olaparib in a Patient with Metastatic Pancreatic Adenocarcinoma with Germline <b><i>BRCA1</i></b> Mutation after Progression on FOLFIRINOX: Case Report and Literature Review

Abstract: Metastatic pancreatic ductal adenocarcinoma (PDAC) has a dismal prognosis. Until recently, cytotoxic chemotherapy was the only treatment option. Currently, there are subgroups of patients with PDAC either with somatic or germline mutations who are candidates for targeted agents. Germline mutations in the BRCA1 and BRCA2 genes promote the incapacity of tumor cells to recover from DNA-accumulated damage caused by cytotoxic drugs, like platinum agents, and, most recently, through a diverse process by poly(adenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Besides, for instance, a clinical study showed that patients with germline BRCA1 mutation underwent disease progression after receiving FOLFIRINOX treatment, but still benefited from olaparib. 24 A similar finding was found in another case, which reported that a patient with a novel somatic BRCA2 point mutation (p. I2315T) also experienced a progressive disease after 6 weeks of first-line chemotherapy and finally acquired an improved progression-free survival after olaparib treatment. 25 These two case reports indicated that patients with germline or somatic BRCA1/2 mutation display poor prognosis before treatment with PARP inhibitors, highlighting the great importance of determining the HRD sub-population before clinical treatment.…”
Section: Discussionsupporting
confidence: 76%
“…Besides, for instance, a clinical study showed that patients with germline BRCA1 mutation underwent disease progression after receiving FOLFIRINOX treatment, but still benefited from olaparib. 24 A similar finding was found in another case, which reported that a patient with a novel somatic BRCA2 point mutation (p. I2315T) also experienced a progressive disease after 6 weeks of first-line chemotherapy and finally acquired an improved progression-free survival after olaparib treatment. 25 These two case reports indicated that patients with germline or somatic BRCA1/2 mutation display poor prognosis before treatment with PARP inhibitors, highlighting the great importance of determining the HRD sub-population before clinical treatment.…”
Section: Discussionsupporting
confidence: 76%
“…PtCh is not only effective in the setting of medical management, as a retrospective study done by Yu et al showed a significantly increased median overall survival and time to progression in BRCA- or PALB2-positive patients taking PtCh perioperatively (adjuvant or neoadjuvant) compared to mutation-negative patients taking PtCh [ 2 ]. However, PtCh agents are not the only effective treatment in BRCA-positive patients; a case reported by Pimenta et al discussed a PDAC patient who showed a significant response to olaparib, a poly(adenosine diphosphate-ribose) polymerase inhibitor (PARPi), as a maintenance drug [ 10 ]. Those drugs inhibit a family of proteins responsible for repairing single-stranded DNA breaks arising during replication [ 11 ] and have been used before on patients with breast and ovarian cancer carrying a BRCA mutation and showed a good response [ 12 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that olaparib and doxorubicin significantly inhibited the cellular proliferation in MDA-MB-468 and NCI-H1703 cells but did not markedly affect the proliferation of MDA-MB-231, HCC1937 and NCI-H520 cells (Figure 5C-D, Figure S13C). Considering the wide clinical applications of olaparib in different types of tumors than doxorubicin (32)(33)(34)(35), we further chose olaparib for further in vivo experiments. The results of in vivo studies showed that olaparib showed remarkable therapeutic efficacy in MDA-MB-468 and NCI-H1703 cell models rather than MDA-MB-231, HCC1937 and NCI-H520 cell models (Figure 5E-I, Figure S13D).…”
Section: Identification Of Olaparib As the Most Promising Therapeutic...mentioning
confidence: 99%